Critical Review of freight Transport Demand Models - Marco Mazzarino (Promet - Traffic&Transportation, 1970)
The importance of freight transport for today's society neednot be underlined. Yet, rather few attempts have been made inorder to model freight transport demand in a quite 'original'and appropriate way, especially if the literature on freight transportis compared with lhe huge amount of works done on passengertransport.The aim of lhe paper is twofold: firs/, a seleclive survey isconducted on the issue of freighttransporl demand modelling,also from an 'evolutionary' standpoint; second, such a body ofliterature is arranged in order to provide an original classificationof available models.